8. Jahresbericht des Instituts für Organisationsökonomik; Eighth annual report of the Institute for Organisational Economics - Alexander Dilger; Milan Frederik Klus (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2018)
Das Institut für Organisationsökonomik (IO) an der Westfälischen Wilhelms-Universität Münster ist inzwischen acht Jahre alt. Der 8. Jahresbericht informiert über das achte Jahr, d. h. über das Wintersemester 2017/2018 und das Sommersemester 2018. Wie in den Vorjahren werden das Institut und seine Angehörigen vorgestellt. Danach wird über die Forschung und Lehre sowie weitere Aktivitäten des Instituts berichtet. – – The Institute for Organisational Economics at the University of Münster is eight years old by now. The eighth annual report informs about the eighth year, the winter semester 2017/2018 and the summer semester 2018. As in the previous years, the institute and its members are presented, followed by reports on research, teaching and further activities of the institute.
Keywords: 650